Efektivitas Penggunaan Media Interaktif Berbasis Powerpoint Terhadap Hasil Belajar Matematika Siswa Kelas V UPT SD Inpres 12/79 Lonrae Kabupaten Bone - Awaluddin Muin; Firdaus Firdaus; Warnida Warnida (STKIP Andi Matappa Pangkep, 2022)
This research is a type of quantitative research with a pre-experimental research design with a One-Group Pretest-Posttest Design which aims to determine students' mathematics learning outcomes and determine whether or not there is a significant difference in students' mathematics learning outcomes before and after using powerpoint-based interactive media. The population in this study were all students of class V UPT SD Inpres 12/79 Lonrae totaling 48 students. The sample used was 48 students who were selected by saturated sampling technique. The data from the research were obtained by giving a test of mathematical questions on the material of building space. The data analysis technique used is non-parametric inferential analysis with the Wilcoxon test because the data is not normal. Students' mathematics learning outcomes obtained before using powerpoint-based interactive media were in the poor category with an average learning outcome of 27.50 and students' mathematics learning outcomes obtained after using powerpoint-based interactive media were in the good category with an average learning outcome of 73 ,85. So it can be concluded that there is significant difference in the use of interactive media based on powerpoint on the mathematics learning outcomes of fifth grade students of UPT SD Inpres 12/79 Lonrae, Bone Regency.